Pendampingan Pastoral Untuk Meningkatkan Spiritual Kaum Tuna Rungu - Maxlucky Tinenti; Stimson Hutagalung; Rolyana Ferinia (JURNAL KADESI, 2021)
God created man with the perfection of the image and image of God, because of sin, the perfection of God is lost, the relationship between God and man is cut off and the physical perfection of man decreases, the limitations of reason, physical and mental deficiencies. One of the physical deficiencies that exist in human nature is deafness or deafness. Due to lack of hearing, deaf people feel inferior, not confident, which results in psychological pressure. The research method uses descriptive qualitative, through journals, articles, internet, books. The purpose of this study, how to rebuild self-confidence and psychological pressure by means of pastoral assistance to improve the spirituality of the deaf by providing motivation through pastoral visitation, training in language so that they can read God's word, equipping skills to be able to be independent entrepreneurs, touching with love and applying the word of God. The result is that deaf people have good spirituality, regain their self-confidence and feel worthy of living before God, in society with existing physical deficiencies